Navigating Paths to Wellness: A Strengths-Based Photovoice Study Conducted with One First Nation in Southern Ontario, Canada - Bryan Tanner; Ningwakwe George; Laura Jane Brubacher; Melody E. Morton Ninomiya; Laura Peach; Sharon Bernards; Renee Linklater; Julie George; Samantha Wells (International Journal of Environmental Research and Public Health, 2022)
Research on substance use challenges in First Nations communities is often deficit-focused and can reinforce paternalistic stereotypes that lead to further discrimination. In this article, we report on findings of a strengths-based Photovoice project done in collaboration with a First Nations’ community in southern Ontario, Canada to better understand experiences with substance use challenges in the community. We analyzed interview data collected with seventeen individuals who have lived experience or are supporting a loved one with lived experience with a substance use challenge. Participants described sources of strength that characterized their path to wellness, including strong family and social connections, cultural practices, identity, spirituality, day-to-day activities, and helpful supports and services. Furthermore, participants made several suggestions for improving services, including the need for integrated and flexible systems of care and trustful client-provider relationships. At its core, nurturing wellness involved a transformative process involving social and/or cultural connections. The stories shared by participants demonstrate the unique and varied strengths drawn from by individuals dealing with a substance use challenge.